Analisis Sarana Pendukung Kepariwisataan Pantai Muara Indah Desa Ogotion Kecamatan Mepanga Kabupaten Parigi Moutong - Nur Aulia Rahmadani; Sri Maryati; M. Iqbal Liayong Pratama (-, 2026)
Tourism development is closely related to the availability of supporting facilities and infrastructure that can provide comfort and satisfaction for visitors. Muara Indah Beach in Ogotion Village, Mepanga District, Parigi Moutong Regency has considerable tourism potential, but the development of supporting tourism facilities is still not optimal. This study aims to analyze the condition of supporting tourism facilities at Muara Indah Beach. The research used a qualitative descriptive approach through literature study, observation, and documentation. The results showed that several tourism supporting facilities are already available, such as parking areas, food stalls, gazebos, public toilets, prayer rooms, and fishing docks. However, the quality and management of these facilities still need improvement. Environmental cleanliness problems, damaged facilities, and limited supporting infrastructure remain the main obstacles in tourism development. On the other hand, mangrove rehabilitation efforts and villa construction indicate positive steps toward sustainable tourism development. The development of planned and sustainable tourism facilities is needed to improve the competitiveness and attractiveness of Muara Indah Beach tourism area.